Delivery of 5′-triphosphate RNA with endosomolytic nanoparticles potently activates RIG-I to improve cancer immunotherapy. (31st October 2018) - Jacobson, Max E.; Wang-Bishop, Lihong; Becker, Kyle W.; Wilson, John T.
Abstract : Delivery of a 5′ triphosphate RNA (3pRNA), a ligand for RIG-I, with endosomolytic nanoparticles (NP) augments response to anti-PD1 immune checkpoint blockade. Abstract : RNA agonists of the retinoic acid gene I (RIG-I) pathway have recently emerged as a promising class of cancer immunotherapeutics, but their efficacy is hindered by drug delivery barriers, including nuclease degradation, poor intracellular uptake, and minimal access to the cytosol where RIG-I is localized. Here, we explore the application of pH-responsive, endosomolytic polymer nanoparticles (NPs) to enhance the cytosolic delivery and immunostimulatory activity of synthetic 5′ triphosphate, short, double-stranded RNA (3pRNA), a ligand for RIG-I. Delivery of 3pRNA with pH-responsive NPs with an active endosomal escape mechanism, but not control carriers lacking endosomolytic activity, significantly increased the activity of 3pRNA in dendritic cells, macrophages, and cancer cell lines. In a CT26 colon cancer model, activation of RIG-I via NP delivery of 3pRNA induced immunogenic cell death, triggered expression of type I interferon and pro-inflammatory cytokines, and increased CD8 + T cell infiltration into the tumor microenvironment. Consequently, intratumoral (IT) delivery of NPs loaded with 3pRNA inhibited CT26 tumor growth and enhanced the therapeutic efficacy of anti-PD-1 immune checkpoint blockade, resulting in a 30% complete response rate and generation of immunological memory that protected against tumor rechallenge. Collectively, these studies demonstrate that pH-responsive NPs can be harnessed to strongly enhance the immunostimulatory activity and therapeutic efficacy of 3pRNA and establish endosomal escape as a critical parameter in the design of carriers for immunotherapeutic targeting of the RIG-I pathway.